Effectivenes of organic and inorganic fertilizer in enhancing growth of ipomoea aquatica (water spinach) in two different types of soil - Jamaludin, Ameelya Farzana; Tajudin, Nur Shuhada; Shahar, Rozilawati; Che Amri, Che Nurul Aini; Zulkifli, Mazidah; Jamaludin, Mayzaitul Azwa (Zibeline International Publishing, 2021)
Planting a crop with high productivity and quality while ensuring the continuity of good soil quality and environmental sustainability is important. With the changes of climate and extensive anthropogenic activities, soil had become undesirable for crops planting. However, various measures can be done to improve this such as applying suitable types of fertilizer and soil amendments besides monitoring the quality of soil continuously. Fertilizer application in a way is helpful in providing essential nutrients needed by the plant while soil organic amendment able to improve its quality through biotic and physical changes. In this study, different combination of treatments was applied in two different types of soil to observe its effect on morphological growth of water spinach (Ipomoea aquatica), soil pH, and total organic carbon (TOC) in soil. Field experiment was conducted at Glasshouse Nursery Complex (GNC), International University Malaysia for five weeks. Combination of treatments consist of control (T1), biochar (T2), chicken manure (T3), combination of biochar and chicken manure (T4), and combination of biochar, chicken manure, and NPK fertilizer (T5). Two types of soil that were used in this study which are normal topsoil and oxisols type of soils. Results showed that the T5 were observed to have the highest average of plant grown in both normal top soil and oxisols soil. The pH of both soils treated with biochar and organic manure increased compared to control which reflect a positive effect towards nutrient availability for plant. Total organic carbon content also showed an increased trend with soil amendment and fertilizer applications. Hence, in overall growth of Ipomoea aquatica improved with application of fertilizer and organic amendments.